English English: English - Gifar, Abdalah; Agustine, Herlina; Bakry, Gema Nusantara (representamen, 2025)
This study discusses the business resilience strategies of local media, namely Ayo Media Network with its portal AyoBandung.com and BandungBergerak.id which have different business approaches during and after the 2024 political year amidst media disruption. The intense political issues in 2024 with the holding of legislative and presidential elections, as well as simultaneous regional head elections are the background for the resilience efforts of the two media to be able to survive and maintain the sustainability of their businesses, and how they will continue after the 2024 political year amidst the media disruption conditions that occur as a critical impact of the development of social media and changes in media audience consumption behavior. By using a qualitative research paradigm approach and case study method, this study highlights how organizational resilience and digital transformation are applied in the business strategies of the two local digital media. Through interviews, observations, and document analysis, the main findings of this study are the similarities between the two media in strategizing diverse revenue streams not only from advertising on their news portals. The difference is, Ayo Media Network relies on media service innovation to adjust to market needs and utilizes an integrated multiplatform network as a bargaining power for advertisers or clients. Meanwhile, BandungBergerak.id focuses on the quality of journalistic content by maintaining its independence, especially from political influence, and accompanies community movements by opening up revenue opportunities from businesses outside of advertising. This research provides insight into the sustainability of media, in this case local digital media that is not affiliated with political forces, to remain relevant and competitive in a media industry that is increasingly being eroded by disruption.